2005
DOI: 10.1007/s11249-005-8308-9
|View full text |Cite
|
Sign up to set email alerts
|

Tribochemical Reactions between Methylated Diamond (111) Surfaces: A Theoretical Study

Abstract: The possibility of tribochemical reactions between methylated diamond surfaces was studied by quantum chemical HartreeFock and B3LYP methods. Lateral sliding of two diamond surfaces cleaved from the diamond crystal lattice and substituted with methyl groups was performed at planar distances of 400 and 350 pm for two models, C 28 H 48 and C 46 H 72 . In each case, the calculations suggest that tribochemical reaction is possible. At planar distance of 400 pm, the reaction occurs within a diamond plane, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…As atomic‐scale interlayer friction can be correlated with the variation of potential energy during the sliding process (Zhong & Tománek, ), the method of calculating variations in potential energy is often applied to the research of frictional characteristics at real contact in solid lubricants (Koskilinna et al, , , ; Neitola et al, ; Wang et al, ) and solid interfaces (Neitola & Pakkanen, ). As these studies showed good agreement with experimental and other theoretical studies, this method is widely applied to the studies of atomic‐scale frictional characteristics of other solid lubricants (Cahangirov et al, ; Levita et al, ; Liang et al, ; Reguzzoni et al, ; Wang et al, ; Wang et al, ), solid interfaces or surfaces (De Barros Bouchet et al, ; Feldbauer et al, ; Garvey, Furlong, et al, ; Garvey, Weinert, et al, ; Garvey et al, ; Koskilinna et al, ; Neitola & Pakkanen, ; Sun et al, ; Wolloch et al, ), the tip motion of the atomic force microscope (Gao et al, ), and single‐crystal muscovite surfaces (Sakuma et al, ). In this study, we applied this method to brucite (Mg(OH) 2 ), which is one of the simplest sheet‐structure minerals.…”
Section: Introductionsupporting
confidence: 59%
“…As atomic‐scale interlayer friction can be correlated with the variation of potential energy during the sliding process (Zhong & Tománek, ), the method of calculating variations in potential energy is often applied to the research of frictional characteristics at real contact in solid lubricants (Koskilinna et al, , , ; Neitola et al, ; Wang et al, ) and solid interfaces (Neitola & Pakkanen, ). As these studies showed good agreement with experimental and other theoretical studies, this method is widely applied to the studies of atomic‐scale frictional characteristics of other solid lubricants (Cahangirov et al, ; Levita et al, ; Liang et al, ; Reguzzoni et al, ; Wang et al, ; Wang et al, ), solid interfaces or surfaces (De Barros Bouchet et al, ; Feldbauer et al, ; Garvey, Furlong, et al, ; Garvey, Weinert, et al, ; Garvey et al, ; Koskilinna et al, ; Neitola & Pakkanen, ; Sun et al, ; Wolloch et al, ), the tip motion of the atomic force microscope (Gao et al, ), and single‐crystal muscovite surfaces (Sakuma et al, ). In this study, we applied this method to brucite (Mg(OH) 2 ), which is one of the simplest sheet‐structure minerals.…”
Section: Introductionsupporting
confidence: 59%
“…Pakkanen reported the reactions of two methylated diamond surfaces and found that the cleavage of C−C surface bonds and the subsequent new bond formation could form carbon debris on the sliding interface. 39 Similarly, bond formation and breaking of C−C covalent bonds at the diamond surfaces initiate high shear forces. In contrast, the surfaces coated with −OH and −H tend to reduce the work of adhesion and shear strength.…”
Section: Tribochemical Reactions By Quantummentioning
confidence: 99%
“…They placed two of these systems in contact and calculated the energy at various points along the sliding path with a load applied normal to the sliding direction. These methods have been employed by the Pakkanen group to study interactions with hydrogen- [132], methyl- [133], and fluoro-terminated [134] diamond surfaces, other hydrocarbons [135], graphene sheets [136], boron nitride [137], and boron nitride on ice [138]. Others have studied the slip behavior of materials using a similar methodology to that used by the Pakkanen group, but using larger model systems.…”
Section: Pes Scans Along the Slip Pathmentioning
confidence: 99%